Study protocol to assess the impact of an integrated nutrition intervention on the growth and development of children under two in rural Bangladesh - Ara, Gulshan; Sanin, Kazi Istiaque; Khanam, Mansura; Sarker, Shafiqul Alam; Khan, Sihan Sadat; Rifat, Mahfuza; Chowdhury, Imran Ahmed; Askari, Sufia; Afsana, Kaosar; Ahmed, Tahmeed (BMC, 2022)
This article was published in BMC Public Health [ © The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s12889-019-7777-y The Journal's website is at: https://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-019-7777-y#citeas